Electrocatalyst for efficient nitrite reduction
The synthesis of IrNi-based nanostructures by simple one-step solvothermal method has solved the problems of low ammonia yield and poor selectivity in the nitrite reduction reaction of existing electrocatalysts, achieving efficient and stable nitrite reduction to produce ammonia, showing excellent catalytic performance and durability.
Patent Information
- Application Number
- CN202411152177.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-05
- Filing Date
- 2024-08-21
- Publication Date
- 2025-08-12
AI Technical Summary
In the nitrite reduction reaction, the existing electrocatalysts have low ammonia yield, poor Faraday efficiency and ammonia selectivity, large overpotential and insufficient stability, making it difficult to achieve efficient nitrite reduction.
A simple one-step solvent thermal method was used to synthesize IrNi-based nanostructures with unconventional tightly arranged hexagonal stacking phases, including IrNi, IrRhNi and IrFeNi nanobranches. By controlling the reduction and sonication of the metal precursor in the solvent, a nickel-rich core and iridium-rich shell structure was formed, and the Ir-Ni interaction was optimized to improve catalytic performance.
High selectivity and efficient nitrite reduction to produce ammonia, with an ammonia Faraday efficiency reaching 98.2%, a generation rate of 34.6 mg h-1 mgcat-1, and it remains efficient under low concentration nitrite conditions, showing excellent catalytic durability and electron transfer efficiency.
Smart Images

Figure CN120465039A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 551,538, filed on February 9, 2024, and U.S. Patent Application No. 18 / 764,392, filed on July 5, 2024, and the disclosures of which are incorporated herein by reference in their entireties. Technical Field
[0002] The present invention generally relates to the fields of nanomaterial synthesis, electrocatalysis and ammonia synthesis. Background Art
[0003] Human activities such as over-fertilization and fossil fuel combustion have seriously disrupted the balance of nitrogen cycle, posing a major threat to human health and the environment. In particular, nitrite (NO2 - ), a key intermediate in the nitrogen cycle, is classified as a Class 2A carcinogen by the World Health Organization (WHO). It can cause serious illnesses such as blue baby syndrome, cell degeneration, and hypertension. Therefore, there is an urgent need to convert harmful nitrite into harmless and useful products to restore the balance of the nitrogen cycle and maintain the sustainable development of global ecosystems.
[0004] Ammonia (NH3) is not only of global importance in agriculture, pharmaceutical industry and chemical engineering, but is also regarded as a long-term carbon-free energy carrier for sustainable energy storage systems due to its high energy density (4.32 kWh / L) and large hydrogen storage capacity (17.6 wt.%). Traditionally, ammonia is produced by the Haber-Bosch process, which involves an energy-intensive reaction of nitrogen with hydrogen at high temperature (300-500°C) and high pressure (20-25 MPa). As an attractive alternative, electrochemical synthesis of ammonia has attracted widespread attention due to its mild operating conditions and compatibility with renewable electricity resources. This method requires only low energy input and can avoid fossil fuel consumption and greenhouse gas emissions.
[0005] Electrocatalytic nitrite (NO2 - ) reduction reaction (NO2RR) can simultaneously remove nitrite pollutants and generate valuable NH3. However, it should be pointed out that the generation of NH3 by NO2RR is a complex proton-coupled electron transfer process (i.e., NO2 - +7H + +6e - →NH3+2H2O), involving the adsorption / desorption of multiple intermediates, still faces the problems of low activity and poor selectivity.
[0006] To date, although considerable effort has been devoted to tuning the size, composition, defects, and morphology of catalysts to enhance their performance in NO2RR, the influence of crystal phase, a key structural parameter, remains largely unexplored. Therefore, developing high-performance electrocatalysts for efficient nitrite reduction is of great significance.
[0007] In recent years, crystal phase engineering has gradually attracted attention as an effective method to regulate the intrinsic physicochemical properties of metal nanomaterials, thereby improving their catalytic activity. To date, a variety of single-metal nanomaterials with unconventional crystal phases have been obtained, such as face-centered cubic (fcc)-2H-fcc heterogeneous gold, fcc ruthenium, 2H palladium and hexagonal close-packed (hcp) rhodium. These materials exhibit superior catalytic activity in different electrochemical reactions than their conventional crystal phase materials. It should be noted that the catalytic performance of single-metal nanomaterials is usually limited by the types of surface adsorption sites, which makes it difficult to simultaneously adsorb and stabilize multiple intermediates in multi-step reactions (such as NO2RR).
[0008] Noble metal nanomaterials have been extensively studied due to their unique physicochemical properties and potential advantages in various applications, including catalysis. Recent advances in the crystal phase engineering of nanomaterials have shown that noble metal alloys with unconventional crystal phases exhibit superior catalytic performance compared to conventional crystal phase alloys due to their unique atomic arrangement and electronic structure.
[0009] Xu et al.1 used wet chemical reduction of Ir in the presence of oleylamine to 3 + and Ni 2 +, prepared Ni@IrNi nanoparticles (NPs). Lv et al.2 prepared IrNi nanoflowers by wet chemical reduction of IrCl3·xH2O and Ni(acac)2 in oleylamine. However, they all adopted the common face-centered cubic (fcc) phase.
[0010] In this regard, the rational design and fine construction of unconventional crystalline phase alloy nanomaterials composed of different metal elements may be an effective way to optimize their intrinsic properties and further enhance their catalytic performance in NO2RR. Unfortunately, due to the huge differences in redox potential, surface energy, and nucleation / growth behavior of different metal components, the precise synthesis of alloy nanomaterials with unconventional crystalline phases still faces significant challenges. Summary of the Invention
[0011] Currently, due to the kinetic mismatch of multiple steps in the NO2RR process, existing catalysts still cannot meet market demand, mainly due to their low ammonia yield, poor Faradaic efficiency (FE) and ammonia selectivity, large overpotential, and insufficient stability. Therefore, the development of high-performance electrocatalysts for efficient nitrite reduction is of great significance.
[0012] The present invention provides a method for the controlled synthesis of unconventional crystalline phase alloy nanostructures to achieve highly selective electrocatalytic nitrite reduction to ammonia. In particular, the present invention provides an electrocatalyst for efficient nitrite reduction. The electrocatalyst comprises one or more iridium-nickel (IrNi)-based alloy nanostructures having an unconventional hexagonal close-packed phase, each having a nickel-rich core and an iridium-rich shell. The atomic feed ratio of nickel to iridium is between 1:1 and 10:1.
[0013] According to one embodiment, the atomic feed ratio is 10-30 at % of iridium (Ir) and 70-90 at % of nickel (Ni).
[0014] According to one embodiment, the one or more IrNi-based alloy nanostructures include a plurality of rod-shaped nanobranches or nanoparticles.
[0015] According to one embodiment, the one or more IrNi-based alloy nanostructures include IrNi nanodendrites, IrRhNi nanodendrites, or IrFeNi nanodendrites.
[0016] According to one embodiment, the atomic feed ratio is 10-20 at % Ir, 70-80 at % rhodium (Rh), and 1-10 at % Ni.
[0017] According to one embodiment, the atomic feed ratio is 10-20 at % Ir, 70-80 at % iron (Fe), and 10-15 at % Ni.
[0018] According to one embodiment, one or more IrNi-based alloy nanostructures can generate a large amount of active hydrogen for hydrogenation of nitrogen-containing intermediates, thereby reducing the overpotential for ammonia generation.
[0019] According to one embodiment, each of the IrNi-based alloy nanostructures has an average length of 125.6±4.4 nanometers and a median width of 16.6±0.3 nanometers.
[0020] According to one embodiment, the electrocatalyst has an ammonia FE of at least 95% at 0 V (relative to a reversible hydrogen electrode) and an ammonia generation rate of at least 30 mg h at -0.1 V (relative to a reversible hydrogen electrode). -1 mg cat -1 ; Energy efficiency is at least 50% at 0 volts to 0.1 volts.
[0021] According to another embodiment, even at a low concentration of 0.01 M nitrite, the electrocatalyst exhibited an ammonia FE of 93.3% at 0 V (vs. reversible hydrogen electrode).
[0022] According to one embodiment, the electrocatalyst exhibits an ammonia partial current density (j) of at least 40 mA cm-2 at -0.1 V (vs. reversible hydrogen electrode). NH3 ).
[0023] According to one embodiment, the one or more IrNi-based alloy nanostructures exhibit excellent catalytic stability over 20 consecutive electrolysis cycles.
[0024] In a second aspect, the present invention provides a one-step synthesis method for unconventional crystalline phase IrNi-based alloy nanostructures, comprising: co-reducing one or more metal precursors in a solution and performing ultrasonic treatment to obtain a homogeneous solution, wherein the solution contains at least one solvent; adding a reducing agent and a capping agent to the homogeneous solution under vigorous stirring to obtain a growth solution; heating the growth solution from room temperature to 220°C and maintaining it at this temperature for 10-15 hours; and cooling the growth solution to room temperature, and then collecting the unconventional crystalline phase IrNi-based alloy nanostructures.
[0025] According to one embodiment, the one or more metal precursors include an iridium salt, a nickel salt, or a combination thereof.
[0026] According to another embodiment, the one or more metal precursors further include a noble metal precursor to form a homogeneous solution. The noble metal precursor includes a rhodium salt, an iron salt, or a combination thereof.
[0027] According to one embodiment, the at least one solvent is selected from oleylamine (OAm), oleic acid (OA), or a combination thereof.
[0028] According to one embodiment, the reducing agent and the capping agent include a formaldehyde solution.
[0029] According to one embodiment, the concentration of the at least one solvent is in the range of 0.01-0.63M.
[0030] According to one embodiment, the concentration of the reducing agent and the capping agent ranges from 0.1 to 0.8M.
[0031] Compared with existing electrocatalyst synthesis technologies, the present invention provides a simple one-step solvothermal method for the universal synthesis of IrNi-based nanostructures with unconventional hexagonal close-packed (hcp) phases, such as IrNi, IrRhNi, and IrFeNi nanobranch (NB). This method uses Ir, Rh, Fe, and Ni salts as precursors, oleylamine and oleic acid as solvents, and formaldehyde solution as a reducing agent and capping agent. The synthesized hcp IrNi NB consists of a nickel-rich core and an iridium-rich shell. This method has the following advantages: simple operation, high product yield, good reproducibility, and easy large-scale production. These developed hcp IrNi NBs can be used for electrochemical nitrite reduction to synthesize ammonia, and can be used as efficient catalysts for electrocatalytic reactions such as hydrogen evolution reaction (HER) and NO2RR.
[0032] The product yield is very high, and scalability is easily achieved by increasing the solvent volume and the number of reactants. In addition, the prepared hcp IrNi NBs exhibit excellent FE and yield in ammonia synthesis. In particular, the IrNi-based nanostructures with hcp phases exhibited exceptional catalytic performance in NO2RR, with FE and NH3 generation rates of 98.2% and 34.6 mg h, respectively. -1 mg cat -1 (75.5 mg h -1 mg Ir -1 ), and performed well at both 0 V and -0.1 V (vs. reversible hydrogen electrode (RHE)) ( Figure 1 ).
[0033] Taking hcp IrNi NB as an example, continuous cyclic electrolysis tests showed that these hcp IrNi NBs have excellent catalytic durability. Electron spin resonance (EPR) and in situ differential electrochemical mass spectrometry (DEMS) results show that hcp IrNi NB can provide a large amount of active hydrogen for the hydrogenation step and significantly reduce the overpotential of NH3 production. Density functional theory (DFT) calculations reveal that the Ir-Ni interaction in hcp IrNi NB is stronger than that in the fcc phase. Due to the stronger Ir-Ni interaction in hcp IrNi NB than in the fcc phase, the electronic structure of Ni and Ir is optimized, providing more efficient electron transfer in the NO2RR process. hcp IrNi NB can more efficiently generate active hydrogen on the surface, thereby reducing the energy barrier and ensuring excellent NO2RR performance.
[0034] The present invention provides the following major advantages: (1) The method provides a feasible strategy for the controllable preparation of nanomaterials with unconventional crystalline phases. Due to the simplicity of the synthesis process, the reproducibility of the product will be very high. By increasing the solvent volume and the amount of metal precursor, large-scale synthesis can be easily achieved, showing the industrial production potential of hcp IrNi NB in practical applications; (2) The synthesis strategy is a general method for the controllable synthesis of hcp phase IrNi-based nanostructures, including hcpIrNi, IrRhNi and IrFeNi nanostructures; (3) The prepared IrNi-based nanostructures can be used as catalysts in NO2RR, exhibiting high Faradaic efficiency and large ammonia synthesis yield, showing great potential in the field of catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings, in which:
[0036] Figure 1 Depicts an overall comparison between hcp IrNi and fcc IrNi.
[0037] Figure 2A Low-magnification transmission electron microscopy (TEM) image showing hcp IrNi NB. Figure 2B TEM image of hcpIrNi NB is shown. Figure 2C Scanning transmission electron microscopy (STEM) images of hcp IrNi NBs are shown. Figure 2D High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images of typical hcp IrNi NBs are shown. Figure 2E Showing atomic-resolution HAADF-STEM image of a typical hcp IrNi NB. Figure 2F Shown Figure 2E A magnified atomic-resolution HAADF-STEM image of the area marked by the white dashed box in the middle.
[0038] Figure 3 The characteristic stacking sequence of hcp phase and fcc phase in their close packing direction is shown. h The direction is along the fcc direction
[111] f The characteristic stacking sequences of the directions are "AB" and "ABC" respectively.
[0039] Figure 4A Schematic diagram showing hcp IrNi NB. Figure 4B Define the length and median width of the nanodendrimers. Figure 4C The size distribution and Gaussian fitting curves of the length and median width of hcp IrNi NBs are shown.
[0040] Figure 5 exhibit Figure 2A Selected area electron diffraction (SAED) pattern of hcp IrNi NB.
[0041] Figure 6 Figure 3. X-ray diffraction (XRD) characterization of hcp IrNi NB. Characteristic peaks attributable to the hcp phase can be clearly identified in the XRD pattern, confirming the hcp phase of the IrNi NB.
[0042] Figure 7 exhibit Figure 2E Fourier transform (FFT) pattern of a mid-atomic resolution HAADF-STEM image.
[0043] Figure 8A This figure shows the composition analysis of hcp IrNi NBs. The figure includes an energy-dispersive X-ray spectroscopy (EDS) spectrum of the hcp IrNi NBs. The inset table shows the mass and atomic ratios of Ir and Ni. Figure 8B Shown are the HAADF-STEM images of typical hcp IrNi NBs and their corresponding EDS line scan results. Figure 8C Shown are the HAADF-STEM images of hcp IrNi NBs and their corresponding EDS elemental distribution maps.
[0044] Figure 9A Shown are TEM images (left) and SAED patterns (right) of the products obtained using different amounts (2 mg and 8 mg) of Ir(acac)3. Figure 9B TEM images (left) and SAED patterns (right) of the products obtained using different amounts (2 mg and 8 mg) of Ni(acac)2 are shown.
[0045] Figure 10A TEM images of the products obtained without adding Ni(acac)2 while keeping other reaction conditions the same are shown. Figure 10B TEM images of the products obtained when Ir(acac)3 was not added while keeping other reaction conditions the same are shown.
[0046] Figure 11A TEM images of the obtained products at Ni:Ir atomic ratios of 1:2, 1:1, 5:1, and 10:1 are shown. Figure 11B Showing the XRD patterns of the resulting products with different Ni:Ir atomic feed ratios.
[0047] Figure 12EDS spectra of products with different Ni:Ir atomic feed ratios are shown. The inset table shows the weight and atomic ratios of Ir:Ni as determined by EDS and inductively coupled plasma spectroscopy (ICP-OES).
[0048] Figure 13A TEM image showing hcp IrRhNi nanodendrimers. Figure 13B HAADF-STEM image showing hcp IrRhNi nanodendrimers. Figure 13C Atomic-resolution HAADF-STEM image showing hcp IrRhNi nanodendrimers. Figure 13D Show from Figure 13C Generated FFT pattern.
[0049] Figure 14 Shown are the SAED patterns of hcp IrRhNi nanobranches.
[0050] Figure 15 The XRD pattern of hcp IrRhNi nanobranches clearly shows the characteristic peaks attributable to the hcp phase, confirming the hcp phase of the IrRhNi nanobranches.
[0051] Figures 16A-16B High-resolution transmission electron microscopy (HRTEM) image showing hcp IrNi nanodendrimers. Figure 16C The EDS spectrum of hcp IrNi nanodendrimers is shown. The inset table shows the weight and atomic ratios of Ir and Ni.
[0052] Figure 17A High-resolution X-ray photoelectron spectroscopy (XPS) spectrum depicting Ir 4f. Figure 17B Depicts the XPS spectrum of Rh 3d. Figure 17C Shows the XPS spectrum of Ni 2p.
[0053] Figure 18A The composition analysis and EDS spectrum of hcp IrRhNi nanobranch are shown. The inset table shows the weight and atomic ratios of Ir, Rh, and Ni. Figure 18B Shown is a typical HAADF-STEM image of hcp IrRhNi nanobranch and an EDS line scan along the white dashed line. Figure 18C Shown are the HAADF-STEM images of a single hcp IrRhNi nanobranch and the corresponding elemental distribution maps.
[0054] Figure 19A TEM image showing hcp IrFeNi nanodendritic structures. Figure 19B HAADF-STEM image showing hcp IrFeNi nanodendritic structures. Figure 19CThe SAED pattern of hcp IrFeNi nanodendrimers is shown, in which the characteristic diffraction rings of the hcp phase can be clearly identified. Figure 19D The XRD pattern of hcp IrFeNi nanobranches clearly shows characteristic peaks attributable to the hcp phase, confirming the hcp phase of the IrFeNi nanobranches.
[0055] Figure 20 Atomic-resolution HAADF-STEM image showing hcp IrFeNi nanodendrimers.
[0056] Figure 21 Show from Figure 20 Generated FFT pattern.
[0057] Figure 22A Shows the XPS spectrum of Ir 4f. Figure 22B Shows the XPS spectrum of Fe 2p. Figure 22C Shows the XPS spectrum of Ni 2p.
[0058] Figure 23A The composition analysis and EDS spectrum of hcp IrFeNi nanobranch are shown. The inset table shows the weight and atomic ratios of Ir, Fe, and Ni. Figure 23B Shown is a HAADF-STEM image of a typical hcp IrFeNi nanobranch and an EDS line scan along the dashed white line. Figure 23C Shown is the HAADF-STEM image of a single hcp IrFeNi nanobranch and the corresponding elemental distribution map.
[0059] Figure 24 Shown are the Ir 4f XPS spectra of hcp IrNi nanobranches and fcc IrNi nanoparticles.
[0060] Figure 25 Shown are the Ni 2p XPS spectra of hcp IrNi nanodendritic and fcc IrNi nanoparticles.
[0061] Figure 26A The standardized Ir L3-edge X-ray absorption near-edge structure (XANES) spectra of hcp IrNi nanodendritic plants, fcc IrNi nanoparticles, Ir powder, and IrO2 are shown. Figure 26B Fourier transform k2-weighted extended X-ray absorption fine structure (EXAFS) spectra of hcp IrNi nanodendritic branches, fcc IrNi nanoparticles, Ir powder and IrO2 are shown.
[0062] Figure 27Shown are the k2-weighted R-space Ir L3-edge EXAFS spectra of Ir powder, hcp IrNi nanobranches, and fcc IrNi nanoparticles.
[0063] Figure 28A Shown are the normalized Ni K-edge XANES spectra of hcp IrNi nanodendritic plants, fcc IrNi nanoparticles, Ni foil, and NiO. Figure 28B Shown are the Fourier transformed k2-weighted EXAFS spectra of hcp IrNi nanodendritic branches, fcc IrNi nanoparticles, Ni foil, and NiO. Figure 28C Shown are the k2-weighted R-space Ni K-edge EXAFS spectra of Ni foil, hcp IrNi nanodendritic branches, and fcc IrNi nanoparticles.
[0064] Figure 29A Shown are the Ir L3-edge XANES spectra of Ir powder, hcp IrNi nanobranches, and fcc IrNi nanoparticles. Figure 29B Showing the fluctuation transformation of Ni K-edge EXAFS spectra of Ni foil, hcp IrNi nanodendritic and fcc IrNi nanoparticles.
[0065] Figure 30 Linear sweep current (LSV) curves of hcp IrNi nanodendritic and fcc IrNi nanoparticles in 1 M KOH with and without 0.1 M KNO2 are shown.
[0066] Figure 31A Shown are the current densities of hcp IrNi nanodendritic and fcc IrNi nanoparticles measured by galvanostatic amperometry at different potentials. Figure 31B Shows the UV-visible absorption spectra of NH4+ at different concentrations. Figure 31C and 31D The NH3 FE and NH3 yields of hcp IrNi nanobranches and fcc IrNi nanoparticles at different potentials are shown.
[0067] Figure 32 The ammonia partial current density (j) on hcp IrNi nanobranch and fcc IrNi nanoparticles is shown. NH3 ). Partial current density of NH3 for hcpIrNi nanobranches and fcc IrNi nanoparticles at different potentials.
[0068] Figure 33 The half-cell energy efficiency (EE) of hcp IrNi nanobranches and fcc IrNi nanoparticles at different potentials is shown.
[0069] Figure 34AShown are the NH3FE and yield of hcp IrNi nanobranch at different nitrite concentrations at 0 V (vs. RHE). Figure 34B The LSV curves of hcp IrNi nanobranches at different KNO2 concentrations are plotted. Figure 34C Demonstrating the potential-dependent NH3 FE of hcp IrNi nanobranches at different KNO2 concentrations. Figure 34D The NH3 production rate of hcp IrNi nanobranches at different KNO2 concentrations is shown. Figure 34E The half-cell energy efficiency of hcp IrNi nanobranch at different KNO2 concentrations is demonstrated.
[0070] Figure 35A Shown are the LSV curves of hcp IrNi nanobranches at different KOH concentrations. Figure 35B The potential-dependent NH3 FE of hcp IrNi nanobranches at different KOH concentrations is shown. Figure 35C The NH3 production rate of hcp IrNi nanobranches at different KOH concentrations is shown. Figure 35D The half-cell energy efficiency of hcp IrNi nanobranch at different KOH concentrations is shown.
[0071] Figure 36A The NH3 FE and yield of hcp IrNi nanobranches in a neutral electrolyte consisting of 0.5 M K2SO4 and 0.1 M KNO2 at different potentials are shown. Figure 36B Shown are the LSV curves of hcpIrNi nanobranches in an electrolyte consisting of 0.5 M K2SO4 and 0.1 M KNO2. Figure 36C Shown are the galvanostatic amperometric measurements of hcp IrNi nanobranch in an electrolyte consisting of 0.5 M K2SO4 and 0.1 M KNO2.
[0072] Figure 37 The galvanostatic amperometric measurement curves of carbon paper and hcp IrNi nanobranch and the corresponding NH3 production rates in KOH and KOH+KNO2 electrolytes are shown.
[0073] Figure 38 Showing the H NMR of electrolytes containing KNO2 and without KNO2 after electrolysis ( 1 H NMR spectra of the electrolyte after electrolysis at 0 V (vs. RHE) using hcpIrNi nanorods, with and without KNO2.
[0074] Figure 39A The NH3 FE and yield of hcp IrNi nanobranch were determined at 0 V (vs. RHE) using UV-visible spectroscopy (UV-vis) and NMR methods. Figure 39B Show different concentrations 14 NH4 + of 1 H NMR spectrum.
[0075] Figure 40A The galvanostatic amperometric curves of hcp IrNi nanobranch during the cycling stability test are shown. The galvanostatic amperometric curves of hcp IrNi nanobranch during 20 consecutive electrolysis cycles at 0 V (vs. RHE) in an electrolyte composed of 1 M KOH and 0.1 M KNO2. Figure 40B Continuous recycling electrolysis tests of hcp IrNi nanobranch at 0 V (vs. RHE) for NO2RR are demonstrated.
[0076] Figure 41A TEM images of hcp IrNi nanodendritic structures after 20 consecutive electrolysis cycles are shown. Figure 41B exhibit Figure 41A SAED pattern. Figure 41C The corresponding EDS spectrum is shown. The inset table shows the atomic ratio and weight ratio between Ir and Ni.
[0077] Figure 42 The Tafel slopes of hcp IrNi nanodendritic and fcc IrNi nanoparticles in NO2RR are shown.
[0078] Figure 43 The cyclic voltammograms of hcp IrNi nanodendrs and fcc IrNi nanoparticles in 1 M KOH solution are shown in the potential range of 0 to 1.1 V (vs. RHE). The peak area of hcp IrNi nanodendrs (0.109) is 20.7% larger than that of fcc IrNi nanoparticles (0.090).
[0079] Figure 44 hcp IrNi nanobranch and fcc IrNi nanoparticles were shown to be free of NO2 - and NO2 - Electron paramagnetic resonance (EPR) spectrum of 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) under different conditions.
[0080] Figure 45A The electrochemical NO2RR performance of hcp IrNi nanobranch in the presence of different concentrations of tert-butyl alcohol (TBA) is shown. The figure includes the LSV curves of hcp IrNi nanobranch at different TBA concentrations. Figure 45BThe NH3 production rates of hcp IrNi nanobranch over the potential range of 0.3 V to -0.1 V (vs. RHE) are shown, and the results are compared at different TBA concentrations.
[0081] Figure 46A Shown are the in situ differential electrochemical mass spectrometry (DEMS) spectra of hcp IrNi nanobranches in NO2RR. Figure 46B Showing the DEMS spectrum of fcc IrNi nanoparticles in NO2RR. Figure 46C In situ DEMS spectra for the detection of NH2OH, NO, HNO, NH, NH2, and H2 on hcp IrNi nanobranch and fcc IrNi nanoparticles in NO2RR are shown.
[0082] Figure 47 In situ DEMS spectra for detecting N* and NH3 on hcp IrNi nanobranch and fcc IrNi nanoparticles.
[0083] Figure 48 Shown are XRD patterns of products obtained by replacing oleylamine with other molecules.
[0084] Figure 49 Shown are TEM images of products obtained by replacing oleic acid with n-heptanol, benzyl alcohol, and ethylene glycol.
[0085] Figure 50 Shown are the XRD patterns of the products obtained using different amounts of oleic acid while keeping the total volume of oleic acid and oleylamine at 5 mL.
[0086] Figure 51 TEM images of products obtained by replacing the formaldehyde solution with benzaldehyde, a benzaldehyde-water mixture (37% by weight of benzaldehyde), formic acid, a formic acid-water mixture (37% by weight of formic acid), acetaldehyde, and glyoxal are shown.
[0087] Figure 52 Shown are the XRD patterns of the products obtained using different amounts of formaldehyde solution.
[0088] Figure 53A The electron distribution of bonding orbitals and antibonding orbitals of hcp IrNi nanodendritic and fcc IrNi nanoparticles near the Fermi level (EF) is shown. Figure 53B The local density of states (PDOS) of hcp IrNi nanodendritic and fcc IrNi nanoparticles are shown.
[0089] Figure 54 The site-dependent PDOS of Ir-5d orbitals in hcp IrNi nanodendrimers and fcc IrNi nanoparticles are demonstrated.
[0090] Figure 55 The site-dependent PDOS of Ni-3d orbitals in hcp IrNi nanodendrimers and fcc IrNi nanoparticles are demonstrated.
[0091] Figure 56 The PDOS evolution of key intermediates during NO2RR on hcp IrNi nanobranches and fcc IrNi nanoparticles is shown.
[0092] Figure 57 Demonstrating the adsorption of key reactants on hcp IrNi nanobranches and fcc IrNi nanoparticles.
[0093] Figure 58 The adsorption of all intermediates such as NO2*, NO*, NHO*, NHOH*, N*, NH2OH*, NH*, NH2* and NH3* on hcpIrNi alloy is shown.
[0094] Figure 59 Show the reaction energy of NO2RR.
[0095] Figure 60 The reaction energy of NO2RR at an applied potential of -0.10 V is shown.
[0096] Figure 61 Shows a comparison of the energies of water dissociation.
[0097] Figure 62 Shown are the energy barriers of the rate-determining step (RDS) at different active hydrogen (H*) coverages. DETAILED DESCRIPTION
[0098] In the following description, IrNi nanobranch with an unconventional hcp phase (IrNi NB), IrRhNi nanobranch with an unconventional hcp phase (IrRhNi NB), and IrFeNi nanobranch with an unconventional hcp phase (hcp IrFeNi NB) are described as preferred examples. Those skilled in the art will appreciate that modifications, including additions and / or substitutions, may be made without departing from the scope and spirit of the present invention. Certain details may be omitted so as not to obscure the present invention; however, this disclosure is prepared to enable those skilled in the art to practice the teachings herein without undue experimentation.
[0099] The precise synthesis of metal nanomaterials with unconventional phases is crucial for developing high-performance catalysts for a variety of applications. Despite numerous challenges posed by the redox potentials, surface energies, and nucleation / growth behaviors of different metal components, the precise synthesis of alloy nanomaterials with unconventional crystalline phases remains a daunting task. For example, manipulating the atomic arrangement of metal nanomaterials, particularly those involving metal alloy nanostructures with varying redox potentials, remains a significant challenge.
[0100] Therefore, the present invention provides a universal one-pot solvothermal method for the controlled synthesis of IrNi-based nanostructures with unconventional hcp phases. The obtained IrNi-based nanostructures (e.g., hcp IrNi, hcp IrRhNi, and hcp IrFeNi nanobranched structures) have a unique core-shell alloy structure, which contains a Ni-rich core and an Ir-rich shell. The developed hcp IrNi-based nanostructures can be used for electrochemical nitrite reduction to synthesize ammonia.
[0101] The working electrode was prepared as follows: the catalyst dispersed in ethanol was further washed with a mixture of ethanol and n-hexane (1:1 by volume) to remove the surfactant on its surface. Then, 0.8 mg of the catalyst was redispersed in 184 μL of isopropanol, followed by the addition of 16 mL of Nafion solution. It was then sonicated for approximately 1 hour to ensure adequate dispersion of the catalyst. The resulting catalyst slurry was then drop-cast onto a 1 cm² (1 cm × 1 cm) carbon paper. The prepared working electrode was then dried in a vacuum oven at room temperature for approximately 2 hours. The electrode was then used for electrochemical nitrite reduction. The hcp IrNi-based nanostructures exhibited superior catalytic performance compared to the fcc IrNi-based nanostructures in NO₂RR. Notably, the hcp IrNi-based nanostructures exhibited superior NH₃ FE (98.2%) and larger EE (50.1%) at both 0 V and 0.1 V (vs. RHE). Meanwhile, the hcp IrNi-based nanostructures also exhibited an excellent NH3 yield of 34.6 mg h at -0.1 V (vs. RHE). -1 mg_cat -1 (75.5 mg h -1 mg_Ir -1 ). In addition, the hcp IrNi-based nanostructures also exhibited superior catalytic durability over 20 consecutive electrolysis cycles.
[0102] In one embodiment, even at a low nitrite concentration of 0.01 M, an excellent ammonia Faradaic efficiency of 93.3% at 0 volts (vs. RHE) can still be achieved.
[0103] In one embodiment, the hcp IrNi-based nanostructures can still show an excellent Faradaic efficiency of 98.6% and a charge-discharge capacity of 18.7 mg h even under neutral conditions. -1 mg cat -1 Excellent ammonia synthesis yield.
[0104] In a neutral buffer solution consisting of 0.5 M PBS (phosphate buffer solution) and 0.1 M KNO2, the hcp IrNi-based nanostructures exhibited excellent ammonia Faradaic efficiency of 96.3% and 21.8 mg h-ionization efficiency at -0.1 V and -0.5 V (vs. RHE), respectively. -1 mg cat -1 In addition, the pH value of the solution after electrolysis only changed slightly compared with the initial state.
[0105] In one embodiment, hcp IrNi-based nanostructures can generate abundant *H for the hydrogenation of nitrogen-containing intermediates, thereby effectively reducing the overpotential for ammonia production.
[0106] In one embodiment, the Ir-Ni interaction not only optimizes the electronic structure of the catalyst but also enhances the electron transfer efficiency on the hcpIrNi-based nanostructures. The excellent NO2RR performance is attributed to the strong Ir-Ni interaction, which largely promotes the stabilization of key intermediates and the generation of active hydrogen, thereby lowering the reaction energy barrier.
[0107] On the other hand, the present invention provides a facile one-pot solvothermal method for the synthesis of IrNi-based nanostructures with unconventional crystalline phases, which offers a feasible strategy for the rational design of advanced NO2RR electrocatalysts aiming at a sustainable nitrogen cycle.
[0108] On the other hand, this method can also be used to synthesize ternary alloy structures with unconventional hcp phases.
[0109] Examples
[0110] Example 1 - Materials and Methods
[0111] Chemicals and reagents
[0112] All starting chemicals, including solvents, metal precursors, reducing agents, and blocking agents, were obtained from commercial sources. All chemicals and reagents were used directly without further treatment.
[0113] Iridium(III) acetylacetonate (Ir(acac)3, 99%) and sodium nitroferricyanide (C5H4FeN6Na2O3) were purchased from AlfaAesar. Rhodium(III) acetylacetonate (Rh(acac)3, 99%), iron(III) acetylacetonate (Fe(acac)3, 95%), and oleic acid (OA, 99%) were purchased from Sigma-Aldrich. Sodium hypochlorite (NaClO, 0.1 M) solution was purchased from Macklin. Nickel(II) acetylacetonate (Ni(acac)2, 95%), oleylamine (OAm, 80–90%), formaldehyde (HCHO, 37 wt.% in water), isopropyl alcohol (IPA, AR, ≥99.5%), tert-butyl alcohol (TBA, AR, ≥99%), potassium hydroxide (KOH, AR, 99%), potassium nitrite (KNO2, AR, 99%), ammonium chloride (ACS, 99.5%), salicylic acid (AR, 99.5%), sodium citrate (98%), sodium hydroxide (NaOH, AR, 96%), maleic acid (AR, ≥99.0% (HPLC)), 5,5-dimethyl-1-pyrroline-N-oxide (DMPO, 97%), and deuterated water (DO, AR, 99%) were provided by Shanghai Aladdin Biochemical Technology Co., Ltd. Ethanol (absolute, ≥99.9%) and n-hexane (99%) were purchased from Anaqua Global International. All chemicals and reagents were used without further purification. Deionized water used in the experiments was from a Milli-Q Plus system with a resistance of 18.2 MΩ·cm.
[0114] TEM and high-resolution TEM (HRTEM) images were taken on a JEOL-2100F transmission electron microscope operated at 200 kV. Spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images were obtained on a high-resolution spherical aberration-corrected transmission electron microscope (JEOL JEM-ARM200F). Scanning transmission electron microscopy (SEM) measurements were performed on a QUANTA250. Powder XRD patterns were recorded on a Rigaku SmartLab X-ray diffractometer using a Cu Kα X-ray source. X-ray photoelectron spectroscopy (XPS) measurements were performed on a Thermo Scientific Nexsa spectrometer equipped with an Al-Kα radiation system. Data calibration was performed by using the C1s peak at 284.8 eV. X-ray absorption spectroscopy (XAS) measurements were performed in transmission mode at the 1W1B beamline of the Beijing Synchrotron Radiation Source. The radiation was monochromatized by a double-crystal silicon (111) monochromator. Background subtraction and XAS data normalization were performed using the Demeter 0.9.25 software package. The edge energies of the XANES spectra were determined by the derivative maximum at the leading edge of the XANES spectrum. The coordination parameters were obtained by fitting the R-space Fourier transform data using the least squares method in Artemis. Electron paramagnetic resonance (EPR) spectra were recorded using a Bruker EMXnano spectrometer with DMPO as the active hydrogen (H*) scavenger. In situ differential electrochemical mass spectrometry (DEMS) measurements were performed on a Linglu DEMS analysis system from Shanghai Linglu Instrument Co., Ltd.
[0115] method
[0116] NO2RR performance test
[0117] Electrochemical NO₂RR performance testing was performed in an H-type electrolytic cell separated by a proton exchange membrane (Nafion 117). Catalyst-modified carbon paper, platinum sheet, and Ag / AgCl (saturated with KCl) were used as the working electrode, counter electrode, and reference electrode, respectively. All potentials were converted to the reversible hydrogen electrode (RHE) scale using the following formula: E (vs. RHE) = E (vs Ag / AgCl) + 0.197 V + 0.059 × pH (1) The electrolyte used was a solution containing 1 M KOH and 0.1 M KNO2, which was purged with high-purity argon (Ar) for at least 30 minutes before testing. Then, 30 ml of the electrolyte was added to the anode and cathode compartments of the H-type cell, respectively. Linear sweep voltammetry (LSV) curves were obtained at a scan rate of 5 mV / s over a potential range of 0.4 V to -0.2 V (relative to RHE). Amperometric tests were performed for 1 hour at each potential with a stirring rate of 600 rpm.
[0118] Electrochemical in situ DEMS testing
[0119] In situ DEMS tests were performed using a homemade electrochemical cell. Platinum wire, saturated potassium chloride (KCl)-filled silver / silver chloride electrode (Ag / AgCl), and catalyst-modified carbon paper were used as counter electrode, reference electrode, and working electrode, respectively. The electrolyte, consisting of 1M KOH and 0.1M KNO2, was purged with high-purity argon (Ar) for at least 30 minutes before measurement. The mass signal was recorded during the LSV process from 0.4 V to -0.2 V (relative to RHE). After the LSV test was completed, the next round of LSV test and mass signal acquisition was restarted when the mass signal intensity returned to the baseline.
[0120] Ultraviolet-visible (UV-Vis) detection of ammonia
[0121] The concentration of ammonia was detected by spectrophotometry using the reported indophenol blue method. First, 2 ml of the pre-diluted electrolyte was taken and mixed with 2 ml of a 1M sodium hydroxide solution containing 5% by mass salicylic acid and 5% by mass trisodium citrate. Then, the above solution was mixed with 1 ml of a 0.05M sodium chlorate solution and 0.2 ml of a 1% by mass aqueous solution of sodium nitrosoferricyanide. After the above mixed solution was placed in the dark for 2 hours, its absorption spectrum was measured at a wavelength of 654 nm using a UV-vis spectrophotometer (Shimadzu-UV1700). A calibration curve of ammonia concentration and absorbance was prepared using a series of standard NH4Cl solutions.
[0122] Determination of ammonia by NMR
[0123] After 1 hour of electrolysis, the electrolyte was removed and mixed with a certain amount of maleic acid to make the concentration of maleic acid reach 0.4 mg / ml. Then, 0.45 ml of the above solution was mixed with 50 μl of deuterated water (D2O) to perform 1 H-NMR (300MHz) test. 14 NH4Cl prepared a series of different 14 NH4 + Concentration 14 N- 14 NH4 + Solution. By association 14 NH4 + Concentration and H- 14 NH4 + A calibration curve was established based on the relationship between the peak area ratio of H-maleic acid and that of maleic acid.
[0124] Calculate Faradaic efficiency (FE), yield (R), and half-cell energy efficiency (EE)
[0125] In the present invention, the Faradaic efficiencies of NH3, N2H4 and H2 are calculated as follows:
[0126] The yield of NH3 is calculated according to the following formula: Where F is the Faraday constant (96485C / mole); C NH3 represents the concentration of ammonia (mg / L); V is the volume of the electrolyte (L); M NH3 represents the molar mass of ammonia (mg / mol); Q is the total charge (C); m cat is the total amount of catalyst (mg); t is the constant potential test time (h).
[0127] The half-cell energy efficiency is defined as the ratio of chemical energy to applied electrical power and is calculated as follows: represents the equilibrium potential of water oxidation (1.23 V compared to RHE); is the equilibrium potential for the reduction of nitrite to ammonia (0.65 V compared to RHE under alkaline conditions); FE NH3 is the Faradaic efficiency of ammonia; E OER is the applied potential (here the overpotential of water oxidation is assumed to be zero, i.e. 1.23 V compared to RHE); E NH3 Potentials were applied for ammonia production after 85% iR compensation.
[0128] Theoretical calculation settings
[0129] To investigate the superior electroactivity of the unconventional hcp phase in IrNi-based nanostructures, density functional theory (DFT) calculations were performed using the embedded CASTEP software package. To accurately describe the exchange-correlation interaction in the electrocatalyst, the generalized gradient approximation (GGA) and Perdew-Burke-Ernzerhof (PBE) functionals were employed. The plane wave cutoff energy was set to 380 eV by default, based on the selected ultrasoft pseudopotential and hyperfine mass. During energy minimization, the Broyden-Fletcher-Goldfarb-Shannon algorithm and a coarse k-point grid were used for all models. Solvent effects were accounted for using a minimum parameter implicit solvation model employing an isodensity scheme. Based on this scheme, DFT describes the solute, while a medium continuum with a spatially varying dielectric constant represents the solvent. The dielectric constant smoothly approaches the bulk value away from the solute and approaches 1 near the solute.
[0130] The hcp IrNi-based nanostructure is constructed based on the (001) surface of the hcp Ni structure, where the core part contains six layers and the shell part contains two layers. The overall Ni / Ir ratio is 3.8 / 1, which is close to the experimental results, where the core part is rich in Ni and the shell part is rich in Ir. The fcc IrNi is peeled off from the (111) surface of the conventional fcc Ni structure, with a thickness of five layers and a Ni / Ir ratio of 4 / 1. For all catalyst surfaces, The vacuum space is kept to ensure that there is enough space for geometry optimization. During the geometry optimization process, the following criteria are applied to ensure convergence: the Hellmann-Feynman force and the total energy difference should be less than and 5×10 -5 eV / atom.
[0131] Example 2
[0132] Synthesis of unconventional hcp IrNi NB
[0133] 4 mg of Ir(acac)3 and 4 mg of Ni(acac)2 were added to 5 ml of a mixture of OAm and OA (volume ratio of 7.3 / 1), and then ultrasonicated for about 2 hours to obtain a uniform solution. Subsequently, 100 microliters of HCHO solution was added dropwise to the above solution under vigorous stirring. The mixture was then stirred at room temperature for 20 minutes. Subsequently, the prepared growth solution was transferred to a polytetrafluoroethylene-lined autoclave with a capacity of 25 ml and heated from room temperature to 220°C for 14 hours. After the reactor was naturally cooled to room temperature, the final product was collected and centrifuged and washed three times with 3 ml of a mixture of ethanol and hexane (volume ratio of 1 / 2). Finally, the product was redispersed in 3 ml of ethanol for use.
[0134] Synthesis of hcp IrRhNi NB and hcp IrFeNi NB
[0135] First, 4 mg of Ir(acac)3, 0.5 mg of Rh(acac)3 and 4 mg of Ni(acac)2 were added to 5 ml of oleylamine / oleic acid mixture (volume ratio of 7.3 / 1), and then ultrasonicated for about 3 hours to obtain a uniform solution. Subsequently, 100 microliters of HCHO solution was added dropwise to the above solution under vigorous stirring. Then, stirring was continued at room temperature for 20 to 30 minutes until the solution became transparent. Subsequently, the obtained growth solution was transferred to a 25 ml polytetrafluoroethylene-lined autoclave and heated from room temperature to 220°C and maintained at this temperature for 14 hours. After the reactor was naturally cooled to room temperature, the final product was collected and centrifuged three times with 3 ml of ethanol and hexane mixture (volume ratio of 1 / 2). Finally, the product was redispersed in 3 ml of ethanol for use.
[0136] The synthesis process of IrFeNi NB is similar to that of IrRhNi NB, except that Rh(acac)3 is replaced by Fe(acac)3. The obtained product is also redispersed in 3 mL of ethanol for later use.
[0137] Synthesis of face-centered cubic (fcc) IrNi nanoparticles
[0138] In a typical fcc IrNi nanoparticle synthesis process, 8 mg of Ir(acac)3 and 8 mg of Ni(acac)2 were added to 5 mL of OAm. After ultrasonic treatment for about 1 hour, the resulting solution was transferred to a 25 mL Teflon-lined autoclave and heated from room temperature to 220°C and maintained at this temperature for 12 hours. After the autoclave was naturally cooled to room temperature, the final product was collected by centrifugation and washed three times with 3 mL of a mixture of hexane and ethanol (volume ratio 1:1). Finally, the resulting product was redispersed in 2 mL of ethanol for further use.
[0139] Example 3
[0140] Structural characterization of unconventional hcp IrNi-based NBs
[0141] Low-magnification TEM images show the high purity of the prepared hcp IrNi NBs ( Figure 2A The crystal structure was characterized by atomic-resolution HAADF-STEM. TEM and HAADF-STEM images showed that the obtained product was composed of multiple rod-shaped nanobranches ( Figures 2B-2D As shown in the spherical aberration-corrected HAADF-STEM images, there is a clear contrast between the inner and outer regions of the nanodendritic branches, indicating the unique core-shell structure of the hcp IrNi NBs ( Figures 2E-2F ). Figure 2E The magnified HAADF-STEM image in the figure clearly identifies the
[001] h The "AB" characteristic stacking sequence of the direction ( Figure 3 ). and The interplanar spacings of hcp IrNi NB correspond to the (002) h and (010) h noodle.
[0142] according to Figures 4A-4C , the average length and median width of a single nanobranch were 125.6 ± 4.4 nm and 16.6 ± 0.3 nm, respectively.
[0143] The characteristic diffraction rings in the SAED pattern of IrNi NB also confirmed its unconventional hcp phase ( Figure 5 ). Meanwhile, the powder XRD pattern further confirmed the hcp phase ( Figure 6 ). In addition, the FFT spectrum of the hcp phase along the
[110] h zone axis further confirmed the unconventional hcp phase ( Figure 7 ).
[0144] EDS results show that the atomic ratio of Ir is 20.5at%, and the atomic ratio of Ni is 79.5at% ( Figure 8A ). EDS line scan and element distribution analysis revealed the alloy structure of hcp IrNi NB, in which nickel (Ni) is enriched in the core region and iridium (Ir) is enriched in the shell region ( Figures 8B-8C ). This finding is highly consistent with the observation that the lattice spacing in the shell region is larger than that in the core region.
[0145] At the same time, when Ir(acac)3 was replaced by IrCl3(aq) or Ni(acac)2 was replaced by NiCl2·6H2O, hcp IrNi NBs were still successfully obtained. In addition, the amount of Ir(acac)2 in the reaction system may significantly affect the morphology and crystal phase of the nanodendritic structures. Specifically, reducing the amount of Ir(acac)3 by half resulted in the formation of hcp IrNiNBs with low uniformity, while doubling the amount resulted in the formation of fcc IrNi nanoparticles ( Figure 9A In contrast, the amount of Ni(acac)2 has little effect on the morphology and crystal phase of the product ( Figure 9B ).
[0146] The co-reduction of Ir and Ni precursors is crucial for the successful synthesis of hcp nanobranch. In the absence of Ni(acac)2, the yield of the product is very low. This is attributed to the effect of the amino and carboxylic acid functional groups in OAm and OA on Ir. 3 +, which significantly reduces the 3 + / Ir reduction potential, thereby slowing down the Ir 3 On the other hand, if Ir(acac)3 is not added, irregular Ni nanoparticles ( Figures 10A-10B These results indicate that the co-reduction of Ir and Ni is a prerequisite for the synthesis of hcpIrNi NBs.
[0147] Furthermore, by decreasing the Ni / Ir atomic ratio, the morphology changes from nanodendritic to nanoparticles ( Figures 11A-11B ). When the Ni:Ir atomic feed ratio is 1:2, the obtained irregular nanoparticles are in the fcc phase. Figure 12, the final atomic percentage of Ir was 49.2%. As the atomic ratio increased from 1:1 to 10:1, the Ir content in the product gradually decreased (from 30.9% to 4.0%), but still maintained a pure hcp phase. Nanobranches could be obtained when the atomic feed ratio was 2:1 and 3:1. The corresponding Ir / Ni atomic ratios were 20.5 / 79.5 and 12.5 / 87.5. These results indicate that the atomic ratio of the metal precursor is crucial for the synthesis of hcp IrNi NBs.
[0148] The same method was used to prepare hcp IrRhNi NB. TEM and HAADF-STEM images showed that the obtained IrRhNiNB consisted of multiple rod-shaped nanobranches and had a core-shell structure ( Figures 13A-13C ). The measured lattice spacing is 2.17 and They correspond to the (002) of the hcp phase in the core (shell) part respectively. h and (010) h The corresponding FFT spectrum is along
[110] h The diffraction pattern of the hcp phase of the zone axis matches well ( Figure 13D ).
[0149] The SAED spectrum of IrRhNi NB can be assigned to the hcp phase ( Figure 14 ), and this result was also confirmed by XRD patterns ( Figure 15 The hcp structure was further confirmed by the FFT spectrum and characteristic "AB" stacking sequence ( Figures 16A-16B ). The atomic ratio of Ir / Ni is 17.4 / 82.6 ( Figure 16C ).
[0150] XPS spectroscopy confirmed the main metallic states of Ir, Rh, and Ni in hcp IrRhNi NBs ( Figures 17A-17C ). EDS spectrum shows that the atomic ratio of Ir / Rh / Ni is 12.5 / 78.3 / 9.2 ( Figure 18A ). In addition, EDS line scanning and elemental distribution maps confirmed that the hcp IrRhNi NB has a nickel (Ni)-rich core and iridium (Ir)-rich shell structure ( Figures 18B-18C ).
[0151] In addition, hcp IrFeNi NB can also be prepared by replacing Rh(acac)3 with Fe(acac)3. TEM and HAADF-STEM images show that the obtained IrFeNi nanostructures have similar morphologies to IrNi NB and IrRhNi NB ( Figures 19A-19B The hcp IrFeNi NB was confirmed by SAED and XRD patterns ( Figures 19C-19D).
[0152] Furthermore, atomic-resolution HAADF-STEM images clearly show the characteristic atomic arrangement of the hcp phase in the core and shell sites ( Figure 20 The measured lattice spacing is and They belong to the (002) of the hcp phase in the core (shell) part respectively h and (010) h The corresponding FFT spectrum is along
[110] h The hcp of the regional axis is consistent ( Figure 21 ).
[0153] XPS spectra confirmed that Ir, Fe and Ni in IrFeNi NB are mainly in metallic state ( Figures 22A-22C ). EDS spectrum shows that the atomic ratio of Ir / Fe / Ni is 17.5 / 71.1 / 11.4 ( Figure 23A Furthermore, EDS line scan and elemental mapping characterization revealed the alloy structure of hcp IrFeNi NBs, which has an Ir-rich shell and a Ni-rich core ( Figures 23B-23C ).
[0154] Example 4
[0155] Comparison of hcp IrNi NBs and fcc IrNi nanoparticles
[0156] In addition to hcp IrNi NBs, common fcc IrNi nanoparticles with a similar Ir / Ni atomic ratio as hcp IrNi NBs were also prepared. The electronic structures of hcp IrNi NBs and fcc IrNi nanoparticles were analyzed by XPS. Figure 24 As shown in the figure, in hcpIrNi NB and fcc IrNi nanoparticles, Ir mainly exists in the metallic state, and the surface atoms are slightly oxidized. Compared with fcc IrNi nanoparticles, the Ir 4f peak position of hcp IrNi NB shifts to the negative direction by about 0.20 eV, which indicates that the electron density of Ir is higher and the interaction between Ir and Ni is stronger. The Ni 2p XPS spectra of the two samples show that the main valence state of Ni is metallic, which is due to the IrNi alloy structure ( Figure 25 ).
[0157] XAS was further used to study the electronic structure and local coordination environment of the synthesized hcp IrNi NB and fcc IrNi nanoparticles. In the Ir L3-edge XANES spectrum, the white line intensity of hcp IrNi NB and fcc IrNi nanoparticles is close to that of Ir powder, but much lower than that of IrO2, indicating that Ir exists mainly in the metallic state, but with slight oxidation ( Figure 26A ). Figure 26B The k2-weighted Fourier transformed Ir L3-edge EXAFS spectrum is shown. The spectrum of Ir powder is approximately A significant peak appears at , which corresponds to the Ir-Ir scattering path. The main peaks of hcp IrNi NB and fcc IrNi nanoparticles are located at about The Ir-Ir or Ir-Ni bond lengths in hcp IrNi NBs and fcc IrNi nanoparticles are shorter than those in pure Ir powder, which is mainly attributed to the formation of IrNi nanostructures.
[0158] In addition, no obvious Ir-O scattering path was observed, which further indicates that the Ir in hcp IrNi NB and fcc IrNi nanoparticles exists mainly in the metallic state. The fitting results show that the Ir-Ir and Ir-Ni bond lengths of hcp IrNi NB and fcc IrNi nanoparticles are the same (Table 1 and Figure 27 The Ir-Ir and Ir-Ni coordination numbers in hcp IrNi NBs are 5.8 and 4.9, respectively, which are similar to those in fcc IrNi nanoparticles, indicating a high degree of alloying of Ir with Ni. These results indicate that Ir has similar coordination environments in hcp IrNi NBs and fcc IrNi nanoparticles.
[0159] Table 1 - Summary of Ir K-edge EXAFS fitting results: comparison of Ir powder, hcp IrNi NB and fcc IrNi nanoparticles Note: Fitting uses k 2 The weighted R spatial spectrum is performed, and the k range is s0 2 =0.7, R range is R refers to the interatomic distance (the bond length between the central atom and the surrounding coordinating atoms); CN is the coordination number; σ 2 is the Debye-Waller factor (a measure of the degree of thermal and static disorder in the distance between the absorbing and scattering atoms); ΔE0 is the edge energy offset (the difference between the zero kinetic energy value of the sample and the zero kinetic energy value of the theoretical model), which is used to align the calculated theoretical spectrum with the actual measured spectrum on the energy axis; the uncertainty of the fitting parameters includes: the error range of CN is ±20%, the error of R is ±1%, and σ 2 The error for ΔE0 is ±20%, and the error for ΔE0 is ±20%. The R factor is used to evaluate the quality of the fit. *These values are fixed in the EXAFS fit based on the known Ir powder structure.
[0160] like Figure 28A As shown in the Ni K-edge XANES spectra, the white line intensity of hcp IrNi NB and fcc IrNi nanoparticles is slightly higher than that of nickel foil, but significantly lower than that of nickel oxide, indicating that the nickel in the two samples is mainly in the metallic state. 2 The weighted Ni K-edge EXAFS spectra show that there is no obvious Ni-O scattering path in both samples, and the main peak positions in fcc IrNi nanoparticles and hcpIrNi NBs are close to Ni foil, indicating that Ni in these two nanostructures mainly exists in a metallic state ( Figure 28B The fitting results show that the coordination number of Ni-Ni in fcc IrNi nanoparticles and hcp IrNi NBs is much higher than that of Ni-Ir, which indicates that only a small amount of Ni is coordinated with Ir to form an IrNi alloy structure (Table 2 and Figure 28C ). These results are consistent with the unique structure of Ni-rich core and Ir-rich shell observed by TEM and EDS. However, the Ni-Ir coordination number in hcp IrNi NB is larger than that in fccIrNi nanoparticles, indicating that the degree of Ni alloying in hcp IrNi NB is higher. At the same time, the Ni-Ni bond length in hcp IrNi NB is Ni foil of fcc phase and fcc IrNi nanoparticles The bond length in the fcc IrNi nanoparticles is larger, which indicates that the hcp structure is successfully formed. The intensity peaks of the wavelet transformed (WT) Ir L3 edge EXAFS spectra of fcc IrNi nanoparticles and hcp IrNi NB are similar, but the peaks are shifted downward relative to Ir powder, which indicates that an IrNi alloy structure is formed ( Figure 29A In the WT of Ni K-edge, the intensity peaks of fcc IrNi nanoparticles and hcp IrNi NBs are close to those of Ni foil, further confirming the metallic state of Ni ( Figure 29B ).
[0161] Table 2 - Summary of Ni K-edge EXAFS fitting results: Ni foil, hcp IrNi NB, and fcc IrNi nanoparticles Note: Fitting uses k 2 The weighted R spatial spectrum is performed, and the k range is s0 2 =0.78, R range is R refers to the interatomic distance (the bond length between the central atom and the surrounding coordinating atoms); CN is the coordination number; σ 2is the Debye-Waller factor (a measure of the degree of thermal and static disorder in the distance between the absorbing and scattering atoms); ΔE0 is the edge energy offset (the difference between the zero kinetic energy value of the sample and the zero kinetic energy value of the theoretical model), which is used to align the calculated theoretical spectrum with the actual measured spectrum on the energy axis; the uncertainty of the fitting parameters includes: the error range of CN is ±20%, the error of R is ±1%, and σ 2 The error for ΔE0 is ±20%, and the error for ΔE0 is ±20%. The R factor is used to evaluate the quality of the fit. *These values are fixed in the EXAFS fit based on the known Ni foil structure.
[0162] Example 5
[0163] Electrochemical NO2RR performance
[0164] In this example, the prepared hcp IrNi NB and fcc IrNi nanoparticles were used as catalysts for the electrocatalytic NO2 reduction reaction. The electrocatalytic performance was tested in a standard H-type cell using 1M KOH and 0.1M KNO2 solution as electrolyte. Figure 30 As shown in Figure 5, in the presence of KNO2, hcp IrNi NBs exhibit significantly higher current density, indicating that their NO2RR performance is superior to that of fcc IrNi nanoparticles.
[0165] Further potentiostatic tests were performed in the potential range of 0.3 to -0.1 V (vs. RHE) to evaluate the NO2RR performance of hcpIrNi NBs and fcc IrNi nanoparticles. Figures 31A-31B The ammonia faradaic efficiency of hcp IrNi NB at 0V (relative to RHE) reaches 98.2%, which is significantly higher than the ammonia faradaic efficiency of fcc IrNi nanoparticles 87.2%. It is worth noting that the ammonia faradaic efficiency of hcp IrNi NB remains stable at above 90% in a wide potential range from 0.1V to -0.05V (relative to RHE). Figure 31C ).
[0166] Meanwhile, the ammonia yield of hcp IrNi NB is significantly higher, reaching a maximum value of 34.6 mg h at -0.1 V (vs. RHE). -1 mg cat -1 (or 75.5 mg h -1 mg Ir -1 ), is fcc IrNi nanoparticles (17.6 mg h -1 mg cat -1 (or 41.0mgh -1 mgIr -1 ))1.97 times (1.84 times) ( Figure 31D ). Accordingly, the partial current density of ammonia for hcp IrNi NB is superior to that of fcc IrNi nanoparticles, reaching a maximum value of 49.9 mA cm at −0.1 V (vs. RHE). -2 ( Figure 32 ).
[0167] Furthermore, the hcp IrNi NB exhibits significantly higher energy efficiency over the entire potential range, reaching a maximum value of 50.1% at 0.1 V (vs. RHE). Figure 33 Table 3 shows that the hcp IrNi NB exhibits excellent NH3 Faradaic efficiency, energy efficiency, and yield at low overpotential, which is superior to most reported NO2RR catalysts.
[0168] Table 3 - Comparison of the electrochemical NO2RR performance of hcp IrNi NB compared with other reported electrocatalysts
[0169]
[0170] Considering the practical application of nitrite pollution removal, the present invention further explored the effect of nitrite concentration on NO2RR. Impressively, hcp IrNi NB can still maintain its excellent catalytic performance over a wide range of nitrite concentrations. Specifically, as the NO2 concentration decreases from 0.1M to 0.01M, the maximum NH3 Faradaic efficiency and energy efficiency of hcp IrNi NB only slightly decrease, from 98.2% to 93.3% and from 50.1% to 47.3%, respectively. Figures 34A-34E ).
[0171] At the same time, use 0.01M NO2 - The maximum NH3 yield of hcp IrNi NB can reach 10.1 mg h -1 mg cat -1 , showing its good potential for ammonia production in actual wastewater treatment. When the nitrite concentration increased to 0.2M, the selectivity, energy efficiency and yield of NH3 decreased slightly compared with 0.1M, which may be attributed to the insufficient supply of active hydrogen. In addition, the electrochemical NO2RR performance at different hydroxide concentrations was also studied ( Figures 35A-35D ).
[0172] The observations showed that KOH concentration had little effect on ammonia production. In particular, when the KOH concentration was as low as 0.1 M, the hcp IrNi NB still exhibited the highest NH3 FE of 96.8%, energy efficiency of 48.4%, and a yield of 21.1 mg h -1 mg cat -1 Furthermore, under neutral conditions, the hcp IrNi NB achieved a highest NH3FE of 98.6% at −0.3 V (vs. RHE), while 18.7 mg h was obtained at −0.5 V (vs. RHE). -1 mg cat -1 The maximum ammonia yield ( Figures 36A-36C After electrolysis at -0.3 V and -0.5 V (vs. RHE), the pH of the electrolyte changed to 11.71 and 12.38, respectively. These results reveal the great potential of hcp IrNi NB as a catalyst for efficient NH3 production under practical conditions.
[0173] In addition, to confirm the source of nitrogen and the accuracy of NO2RR performance measurements, control experiments were performed using carbon paper and hcp IrNi NB as electrodes. As expected, the amount of NH3 generated on carbon paper was very small regardless of whether KNO2 was added ( Figure 37 ). In contrast, in the absence of KNO2, the current density and NH3 production rate of hcp IrNi NB are almost negligible, but these values increase significantly after the introduction of KNO2. In addition, as shown in the NMR spectra, no difference in the current density and NH4 production rate is observed in the absence of KNO2 in the electrolyte. + The peak of the correlation ( Figure 38 ).
[0174] Importantly, the NH3 FE and yield calculated by UV-visible spectroscopy (UV-vis) were highly consistent with those obtained by the NMR method, indicating the high accuracy and reliability of the electrochemical results ( Figures 39A-39B ). In an electrolyte with pH = 14, the volatilization of NH3 during 1 hour of electrolysis is almost negligible. In addition, potential by-products, including hydrazine (N2H4) and hydrogen (H2), were detected by UV-vis spectroscopy and gas chromatography, respectively. As the applied potential gradually became negative to -0.1 V (relative to RHE), the FE of N2H4 gradually decreased to 0.5%, while the FE of H2 increased to 11.5%. At 0 V (relative to RHE), the amounts of N2H4 and H2 were negligible, which verified the high selectivity of NH3 synthesis.
[0175] The NO2RR reaction stability of hcp IrNi NB was evaluated by continuous cyclic electrolysis tests at 0 V (vs. RHE). The FE and yield of NH3 remained stable over 20 consecutive electrolysis cycles, indicating that hcp IrNi NB has excellent catalytic durability in the NO2RR reaction ( Figures 40A-40B ). It is noteworthy that the morphology, composition, and crystal phase of the hcp IrNi NBs were well maintained after the stability test, as verified by TEM, SAED, and EDS characterizations ( Figures 41A-41C ). In addition, the core-shell structure consisting of a nickel-rich core and an iridium-rich shell was well maintained. The above results confirm the excellent catalytic stability of the unconventional hcpIrNi NB in NO2RR.
[0176] Example 6
[0177] mechanism
[0178] The study showed that the Tafel slope of hcp IrNi NB (131mV dec -1 ) is significantly lower than the Tafel slope of fcc IrNi nanoparticles (172 mV dec -1 ), which indicates that hcp IrNi NB has higher electron transfer efficiency and faster reaction kinetics in NO2RR ( Figure 42 ). The subsequent conversion of NO2 is significantly affected by the rate of generation and consumption of active hydrogen (H*). Figure 43 As shown in Figure 2, the H* area of hcp IrNi NBs is 20.7% larger than that of fcc IrNi nanoparticles, indicating that hcp IrNi NBs can provide more H* to promote NO2 - Converted into NH3.
[0179] To directly confirm the presence of H*, EPR measurements were performed using 5,5-dimethyl-1-pyrrolidine N-oxide (DMPO) as an H* capture agent. During electrolysis without KNO2, hcp IrNi NBs exhibited stronger DMPO-H signals than fcc IrNi nanoparticles, indicating that hcp IrNi NBs possess a stronger ability to generate H*. Upon addition of KNO2, the signal intensity of fcc IrNi nanoparticles decreased only slightly, while the DMPO-H signal intensity of hcp IrNi NBs decreased significantly ( Figure 44 This result indicates that the H* generated on the hcp IrNi NB can be rapidly consumed, thus ensuring the rapid conversion of nitrogen-containing intermediates into NH3.
[0180] In addition, an appropriate amount of tert-butanol was added to the electrolyte to effectively capture the generated H*. As the concentration of tert-butanol increased, the current density and NH3 yield decreased significantly, indicating that the balance between the generation and consumption of H* is crucial for NH3 synthesis ( Figures 45A-45B ).
[0181] In order to gain a deeper understanding of the reaction process of NO2RR, in situ DEMS characterization was also performed. During the five LSV processes, mass / charge (m / z) signals corresponding to H2, N, NH, NH2, NH3, N2, NO, HNO, NH2OH, and NO2 were detected in both hcpIrNi NB and fcc IrNi nanoparticles, which were 2, 14, 15, 16, 17, 28, 30, 31, 33, and 46 ( Figures 46A-46C The reaction pathway of NO2RR is as follows: NO2*→NO*→NOH*(HNO*)→NHOH*(N*)→NH2OH*(NH*)→NH2*→NH3*→NH3. Meanwhile, the H2 peak intensity of hcp IrNi NB is significantly higher than that of fcc IrNi nanoparticles, indicating that they have a stronger ability to generate H* from hydrogenated nitrogen-containing intermediates ( Figure 46C hcp IrNi NB exhibits a low overpotential in the formation of multiple nitrogen-containing intermediates and final products (such as NH2OH, NO, HNO, N, NH, NH2 and NH3). Figure 47 These observations reveal the remarkable catalytic activity of hcp IrNi NB in the generation of H* and the hydrogenation of nitrogen-containing intermediates to NH3.
[0182] Example 7
[0183] Effects of solvent and formaldehyde solution on the synthesis of hcp IrNi NB
[0184] The effect of OAm was studied by replacing it with ODE, octadecylamine (ODA), and hexadecylamine (HDA). When ODE was used as the solvent, IrNi nano-dendrite structures with an Ir / Ni atomic ratio of 61.8 / 38.2 were prepared. No characteristic peaks corresponding to hcp were found in the XRD pattern ( Figure 48 ). When ODA and HDA were used instead of OAm, IrNi nanobranches were formed, and the Ir atomic percentages were as low as 11.8% and 24.9%, respectively. These results indicate that the formation of hcp phase may be related to the final atomic ratio of Ir / Ni in the reaction system. 3+ Strong coordination reduces the Ir 3+ The reduction tendency of Cr(III) leads to a lower Ir / Ni atomic ratio.
[0185] In addition, the effect of OA was also studied. When OA was replaced by n-heptanol and ethylene glycol, only irregular nanoparticles were formed. Although some branched structures were obtained by replacing OA with benzyl alcohol, the uniformity of these products was very poor ( Figure 49 When OA was not added, only nanoparticles with hcp phase were obtained ( Figure 50 As the OA dosage increased from 0.2 mL to 1 mL, the multi-rod-like branched nanostructure was well-maintained, while the Ir / Ni atomic ratio remained almost unchanged, and its crystal phase remained consistently hcp. These results indicate that OA, as a structure-directing agent, plays a key role in the formation of the branched structure.
[0186] Furthermore, formaldehyde plays a dual role in the formation of well-defined nanobranched and unconventional hcp phases ( Figure 51 In the absence of formaldehyde, nanoparticles with fcc phase were formed. After adding 50 microliters of formaldehyde solution, branched nanostructures with coexistence of fcc and hcp phases were obtained. When 100 microliters of formaldehyde solution was added, IrNi nanobranched structures with pure hcp phase were successfully synthesized ( Figure 52 Furthermore, the generation of hydrogen gas with increasing formaldehyde solution dosage resulted in a decrease in the atomic ratio of Ir from 25.6% to 6.3%, which was due to an increase in the formaldehyde solution dosage from 0 to 400 μL. These results indicate that the presence of formaldehyde is crucial for the formation of the hcp phase, and its dosage significantly affects the product morphology.
[0187] Time-dependent experiments were also conducted to investigate the formation mechanism of hcp IrNi NBs. After one hour of reaction, no product was produced. At two hours, nickel-rich polyhedral nanoparticles and branched structures were formed, with an Ir / Ni atomic ratio of 15.7 / 84.3. As the reaction continued, nanostructured branches formed after four hours, likely due to the polycrystalline nature of nickel, and the Ir / Ni atomic ratio decreased slightly to 10.4 / 89.6. At six hours, the morphology of the sample was similar to that observed after four hours, with an Ir / Ni atomic ratio of 14.5 / 85.5. Extending the reaction time to eight and eleven hours resulted in slightly altered product morphology, but the product remained pure hcp. The Ir / Ni atomic ratio increased from 16.3 / 83.7 to 20.0 / 80.0. Finally, after 14 hours, hcp IrNi NBs with an Ir / Ni atomic ratio of 20.5 / 79.5 were obtained.
[0188] Based on the results of the above control experiments and time-dependent experiments, a possible mechanism for the synthesis of hcp IrNi NBs was proposed. 3 + and Ni 2+ is reduced to nickel-rich polyhedral fcc IrNi nanoparticles. Subsequently, due to the synergistic effect of OAM, OA and formaldehyde, nickel-rich IrNi NBs are formed in
[111] f direction gradually grows along
[001] h As the reaction time is further extended, the Galvanic replacement reaction between the nickel-rich nanobranches and the Ir precursor occurs on the surface of the Ni-rich IrNi NB, gradually forming an IrNi NB with a pure hcp structure. 2 + and Ir 3 + is reduced and selectively moves along
[001] h Directional deposition was achieved, and finally hcp IrNiNB with a nickel-rich core and an iridium-rich shell was successfully synthesized.
[0189] Example 8
[0190] Theoretical calculations
[0191] DFT calculations were further used to explore the electronic structure differences and reaction trends of hcp IrNi NBs and fcc IrNi NPs in NO2RR. Figure 53A The surface electron distributions near the Fermi level of hcp and fcc IrNi nanostructures are shown for comparative analysis. The contribution of bonding orbitals on the hcp IrNi surface is significantly stronger than that on the fcc IrNi surface, indicating that the hcp surface has higher electroactivity. After geometry optimization, the hcp surface exhibits significant lattice distortion near the Ir sites, which may be attributed to the strong interaction between the Ir-rich shell and the Ni-rich core. Remarkably, these surface distortion regions affect the surface binding orbitals, thereby significantly modulating the surface activity.
[0192] As a result, the electron transfer efficiency and adsorption performance of key intermediates on the hcp surface are improved, thus supporting fast NO2RR kinetics. In addition, by comparing the shell structures with different Ir:Ni ratios, it is found that increasing Ir concentration leads to an increase in the energy required for formation. The optimal balance between electroactivity and stability is achieved when the concentrations of Ir and Ni in the shell are similar. A more in-depth analysis of the electronic structure of hcp and fcc IrNi nanostructures was carried out using the PDOS method ( Figure 53B In the hcpIrNi NB, it is observed that the Ni-3d orbital dominates the electron density close to the Fermi level, and a slight splitting occurs. At the same time, the Ir-5d orbital shows a wide coverage range, which places the Ni-3d orbital in the middle. This ensures that the nickel on the surface has a stable valence state during the electrocatalytic process. The e in the Ir-5d orbital g -t2g The splitting is almost non-existent, indicating that the energy barrier for electron transfer on the hcp IrNi NB surface is smaller. In contrast, for fcc IrNi NPs, the Ni-3d orbitals remain similar, but the e g -t 2g The splitting becomes more obvious with an energy barrier of 0.98 eV, which leads to a decrease in the electron transfer efficiency. V -1.80eV(E V = 0eV) slightly shifted to the E on the fcc IrNi nanostructure V This indicates that the Ir sites in the hcp phase have a slightly higher valence state, making them more electroactive in electron transfer with intermediates, thereby promoting the NO2RR reaction.
[0193] Furthermore, the site-dependent PDOS of Ir in hcp and fcc IrNi were compared to reveal their different electronic structures ( Figure 54 For Ir-5d orbitals, e can be clearly observed in both Ir metal bulk and fcc phase IrNi nanostructures. g -t 2g However, in hcp IrNi NB, e g -t 2g The splitting is significantly weakened, especially in the shell part of the core-shell structure. From the core-shell interface to the shell surface, e g -t 2g The energy barrier for splitting is significantly reduced, and the electron density near the Fermi level increases, indicating efficient electron transfer behavior. This is attributed to two strong interactions: core-shell interaction and Ir-Ni interaction. For Ni-3d orbitals, both the hcp phase and the fcc phase show electronic structures similar to those of metallic Ni, indicating that the Ni site is close to the metallic state ( Figure 55 ). Compared with the fcc phase and bulk metal, the Ni-3d orbital in the hcp phase is slightly shifted downward, which is caused by the stronger interaction between Ni and Ir. The superior electroactivity of hcp IrNi stems from the higher alloying level, which leads to more intense electron transfer between Ir and Ni, thereby optimizing the adsorption of key intermediates and accelerating the NO2RR reaction. With the optimized electronic structure, the hcp IrNi surface should exhibit different adsorption behavior from the fcc IrNi surface, which can be distinguished by the change in the PDOS of the key intermediates ( Figure 56During the initial activation of NO2*, hcp IrNi exhibits a good linear relationship, which ensures rapid electron transfer in each reaction step. In contrast, it is observed that the s and p orbitals of N* adsorbed on the fcc IrNi surface deviate more significantly from the linear relationship, which leads to an increased energy barrier during the NO2RR process.
[0194] At the same time, the reaction trend of NO2RR was discussed from the energy aspect. - The adsorption energy of H* is lower than that of fcc IrNi nanoparticles, which is crucial for the rapid start of the NO2RR process ( Figure 57 Meanwhile, the affinity of hcp IrNi NB for NO2- is much stronger than that for H*, thus suppressing the hydrogen evolution reaction (HER).
[0195] Further adsorption configuration analysis revealed that NO2- prefers to be stabilized on the hollow active sites and dissociates into NO* there, which supports the excellent electrocatalytic activity of hcp IrNi NB ( Figure 58 ). As the reduction process proceeds, the most stable adsorption sites of the key intermediates gradually shift from hollow sites to bridging sites and nickel top sites until the final reaction step. fcc IrNi nanostructures also show a preference for hollow sites. Therefore, compared with fcc IrNi nanoparticles, hcp IrNi NBs show a more favorable overall reaction trend in the NO2RR reaction, with a lower energy barrier ( Figure 59 ).
[0196] In the NO2RR process, whether in the hcp or fcc phase, the main energy barrier appears in the reduction step of HNO*. The energy barrier of the NHOH* path is lower than that of the N* path, indicating that the formation of N* is the rate-limiting step (RDS). hcp IrNi shows a much lower energy barrier than fcc IrNi (0.28eV vs. 0.79eV), which makes hcp IrNi more efficient in the NO2RR process and has a higher yield of NH3. hcp IrNi is able to eliminate all energy barriers through the NHOH* reaction path at an applied potential of -0.10V, showing more efficient NO2RR performance than fcc IrNi at the same potential ( Figure 60 ).
[0197] In addition, the effect of active hydrogen on the water dissociation energy barrier was revealed ( Figure 61The energy barrier for the generation of active hydrogen by hcp IrNi NB is 0.24 eV, which is lower than the 0.30 eV of fcc IrNi nanoparticles. This confirms that there are more H* on the surface of hcp IrNi, which promotes the reaction of NO2RR. As H* is generated on the catalyst surface, the coverage of H* will also affect the energy barrier of the rate-determining step of NO2RR ( Figure 62 With increasing H* coverage, the energy barrier for the rate-determining step on the hcp IrNi NB decreases from 0.28 eV to a minimum of 0.21 eV at an H* coverage of 1 / 9. With increasing H* coverage, the RDS energy barrier increases to 0.48 eV at 1 / 3 H* coverage, likely due to blocked active sites. This suggests that optimal H* coverage can enhance the performance of the NO2RR.
[0198] With NO2 - Unlike hcp IrNi, H* prefers to adsorb on the bridging sites of hcp IrNi to avoid blocking the surface active sites. - The competition between H* and H* on similar active sites becomes more intense, which reduces the performance of NO2RR and enhances the competing HER process. In addition, when the H* coverage reaches 1 / 3, the HER performance may be affected by the significantly increased energy cost. With the generation of H* on the catalyst surface, the H* coverage not only induces stronger surface distortion, but also affects the energy barrier of the rate-determining step of NO2RR ( Figure 62 ).
[0199] In summary, the unconventional hcp IrNi NB of this invention features efficient precious metal utilization, thanks to the alloying effect and the construction of an unconventional crystal structure. Compared to other catalysts, it not only exhibits superior catalytic performance, faster reaction kinetics, higher yields, but also improved long-term durability, demonstrating outstanding potential in relevant catalytic reactions. Potential markets for this invention include electrocatalysts and electrochemical ammonia synthesis.
[0200] The above description of the present invention is for illustration and description purposes only and is not intended to be an exhaustive list of all possible forms or to limit the specific embodiments of the invention. Many modifications and variations will be apparent to those skilled in the art.
[0201] These embodiments are chosen and described in order to best explain the principles of the invention and its practical applications, thereby enabling those skilled in the art to understand the invention for various embodiments and with various modifications as are suited to particular use.
[0202] definition
[0203] Throughout this specification, unless the context requires otherwise, the word "comprise" or variations such as "comprises" or "comprising" will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers. It should also be noted that in this disclosure and particularly in the claims and / or paragraphs, terms such as "comprises," "comprised," "comprising," etc. may have the meanings ascribed to them in U.S. patent law; for example, they allow for elements not expressly recited but exclude elements that are found in the prior art or that affect the basic or novel characteristics of the invention.
[0204] Furthermore, throughout the specification and claims, unless the context requires otherwise, the word "include" or variations such as "includes" or "including", will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.
[0205] As used herein and not otherwise defined, the terms "substantially," "essentially," "approximately," and "about" are used to describe and take into account minor variations. When used in conjunction with an event or circumstance, the terms can encompass instances where the event or circumstance definitely occurs as well as instances where the event or circumstance closely approximates to occurring. For example, when used in conjunction with a numerical value, the terms can encompass a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.
[0206] References in this specification to "one embodiment," "an embodiment," "an exemplary embodiment," etc., indicate that the described embodiment may include a particular feature, structure, or characteristic, but not every embodiment may include the particular feature, structure, or characteristic. Furthermore, such phrases do not necessarily refer to the same embodiment. Furthermore, when a particular feature, structure, or characteristic is described in conjunction with an embodiment, it should be understood that it is within the knowledge of those skilled in the art to affect such feature, structure, or characteristic in conjunction with other embodiments, whether or not explicitly described.
[0207] In the preparation methods described herein, except where a chronological order or sequence of operations is explicitly stated, the steps may be performed in any order without departing from the principles of the present invention. Reciting in the claims the effect of performing a step first and then subsequently performing several other steps should mean that the first step is performed before any of the other steps, but the other steps may be performed in any suitable sequence unless the sequence is further stated within the other steps. For example, a claim element stating "step A, step B, step C, step D, and step E" should be interpreted to mean that step A is performed first and step E is performed last, and steps B, C, and D may be performed in any order between step A and step E, and the order still falls within the literal scope of the method claimed. A given step or subset of steps may also be repeated. In addition, unless the claim language explicitly states that a specified step is performed separately, the steps may be performed simultaneously.
[0208] "hcp IrNi-based nanostructures" refer to nanostructures composed of an alloy of iridium (Ir) and nickel (Ni) with a hexagonal close-packed (hcp) crystal structure. "IrNi-based" indicates that these nanostructures are primarily composed of Ir and Ni, but may also include other metals.
[0209] "Atomic percent" or "at%" refers to the percentage of atoms of each element in a composition relative to the total atoms. The sum of the atomic percent of each element in a composition should equal 100%.
[0210] The reversible hydrogen electrode (RHE) is a commonly used reference electrode in electrochemical measurements. The potential of the RHE is set to 0 volts under standard conditions. When electrochemical potentials are reported "relative to the RHE," it means that the measured potential is compared relative to the potential of the RHE. This standardized approach allows for consistent and comparable reporting of electrochemical potentials across different experiments and conditions.
[0211] Other definitions of selected terms used herein can be found within the detailed description of the invention and are applicable to the entire text. Unless otherwise defined, all other technical terms used herein have the same meaning as those generally understood by those skilled in the art to which the invention pertains.
[0212] References: The disclosures of the following references are incorporated by reference 1. Xu, J., Wang, X., Mao, X., Feng, K., Xu, J., Zhong, J., ... & Li, Y. (2023). Prominent electronic effect in iridium alloy-coated nickel nanoparticles enhances alkaline hydrogen electrocatalytic performance. in iridium-alloy-skinned nickel nanoparticles boosts alkalinehydrogen electrocatalysis). Energy & Environmental Science, 16(12), 6120-6126. 2. Lv, F., Zhang, W., Yang, W., Feng, J., Wang, K., Zhou, J., ... & Guo, S. (2020). Ir-based alloy nanoflowers with optimized hydrogen binding energy as bifunctional electrocatalysts for enhanced overall water splitting performance. alloy nanoflowers with optimized hydrogen binding energy asbifunctional electrocatalysts for overall water splitting). Small Methods,4(6),1900129.
Claims
1. An electrocatalyst for efficient nitrite reduction, characterized in that: The electrocatalyst comprises one or more iridium-nickel-based alloy nanostructures having an unconventional close-packed hexagonal stacking phase, wherein the one or more IrNi-based alloy nanostructures having an unconventional close-packed hexagonal stacking phase comprise a nickel-rich core and an iridium-rich shell, the atomic feed ratio of the nickel to the iridium being between 1:1 and 10:1, and the electrocatalyst having an ammonia Faradaic efficiency of at least 95% at 0 volts relative to a reversible hydrogen electrode and an ammonia generation rate of at least 30 mg h-1 at -0.1 volts relative to the reversible hydrogen electrode. -1 mg cat -1 ; An energy efficiency of at least 50% at 0 volts to 0.1 volts relative to the reversible hydrogen electrode.
2. The electrocatalyst according to claim 1, wherein the atomic feed ratio is 10-30 at% of iridium and 70-90 at% of nickel.
3. The electrocatalyst of claim 1, wherein the one or more iridium-nickel based alloy nanostructures comprise a plurality of rod-shaped nanobranches or nanoparticles.
4. The electrocatalyst of claim 2, wherein the one or more iridium-nickel based alloy nanostructures comprise IrNi nanodendrs, IrRhNi nanodendrs, or IrFeNi nanodendrs.
5. The electrocatalyst according to claim 4, wherein the atomic feed ratio is 10-20 at% of iridium, 70-80 at% of rhodium and 1-10 at% of nickel.
6. The electrocatalyst according to claim 4, wherein the atomic feed ratio is 10-20 at% of iridium, 70-80 at% of iron, and 10-15 at% of nickel.
7. The electrocatalyst of claim 1, wherein the one or more iridium-nickel based alloy nanostructures are capable of generating a large amount of active hydrogen for hydrogenation of nitrogen-containing intermediates, thereby reducing the overpotential for ammonia production.
8. The electrocatalyst according to claim 1, wherein each iridium-nickel-based alloy nanostructure has an average length of 125.6±4.4 nm and a median width of 16.6±0.3 nm.
9. The electrocatalyst of claim 1, wherein the electrocatalyst exhibits an ammonia faradaic efficiency of 93.3% at 0 volts relative to the reversible hydrogen electrode even under a low nitrite concentration condition of 0.01 M.
10. The electrocatalyst of claim 1 , wherein the electrocatalyst exhibits an ammonia partial current density (j) of at least 40 mA cm-2 at -0.1 volts relative to the reversible hydrogen electrode. NH3 ).
11. The electrocatalyst of claim 1 , wherein the one or more iridium-nickel based alloy nanostructures exhibit catalytic stability over 20 consecutive electrolysis cycles.
12. A one-step synthesis method of unconventional crystalline phase iridium-nickel based alloy nanostructures, characterized in that: The one-step synthesis method comprises: co-reducing one or more metal precursors in a solution and sonicating to obtain a homogeneous solution, wherein the solution comprises at least one solvent; adding a reducing agent and a capping agent to the homogeneous solution under vigorous stirring to obtain a growth solution; The growth solution is heated from room temperature to 220° C. and maintained for 10-15 hours; The growth solution is cooled to room temperature, and then the unconventional crystalline phase iridium-nickel based alloy nanostructures are collected.
13. The one-step synthesis method according to claim 12, wherein the one or more metal precursors comprise iridium salts, nickel salts or a combination thereof. The one-step synthesis method according to claim 13 , wherein the one or more metal precursors further comprise a noble metal precursor to form the homogeneous solution. The one-step synthesis method according to claim 14 , wherein the noble metal precursor comprises a rhodium salt, an iron salt or a combination thereof.
16. The one-step synthesis method according to claim 12, wherein the at least one solvent is selected from oleylamine, oleic acid or a combination thereof. The one-step synthesis method according to claim 12 , wherein the reducing agent and the capping agent comprise formaldehyde solution. The one-step synthesis method according to claim 12 , wherein the concentration of the at least one solvent is in the range of 0.01-0.63 M.
19. The one-step synthesis method according to claim 12, wherein the concentration of the one or more metal precursors ranges from 1 to 10 mg.
20. The one-step synthesis method according to claim 12, wherein the concentration of the reducing agent and the capping agent ranges from 0.01 to 0.8 M.